2011
DOI: 10.3346/jkms.2011.26.5.654
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection is Associated with Elevated Low Density Lipoprotein Cholesterol Levels in Elderly Koreans

Abstract: This study was conducted to investigate the association between Helicobacter pylori (H. pylori) infection and the lipid profile among elderly Koreans. A total of 462 subjects (mean age 66.2 ± 7.6 yr, 84% males) who underwent health check-up were investigated. Each subject underwent gastroduodenoscopy with gastric mucosal biopsy, and H. pylori infection was determined by histopathological examination using the updated Sydney System score. The presence of H. pylori infection was significantly associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
4
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 21 publications
8
37
4
5
Order By: Relevance
“…In the present study, HDL-C level was significantly lower in patients (H. pylori seropositive) than in controls (seronegative subjects), total cholesterol, LDL-C and triglyceride level were found to be significantly higher in patients than in controls (P < 0.01). Concerning the changes in serum lipids in seropositive subjects, the results of our study were similar to other studies [14] [17]- [21]. Buzás reported that the increase of cholesterol and LDL-C and decrease of HDL-C levels of infected people creates an atherogenic lipid profile which could promote atherosclerosis with its complications [12].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, HDL-C level was significantly lower in patients (H. pylori seropositive) than in controls (seronegative subjects), total cholesterol, LDL-C and triglyceride level were found to be significantly higher in patients than in controls (P < 0.01). Concerning the changes in serum lipids in seropositive subjects, the results of our study were similar to other studies [14] [17]- [21]. Buzás reported that the increase of cholesterol and LDL-C and decrease of HDL-C levels of infected people creates an atherogenic lipid profile which could promote atherosclerosis with its complications [12].…”
Section: Discussionsupporting
confidence: 90%
“…A very interesting study on 462 elderly Koreans supported the hypothesis that H. pylori infection plays a role in promoting atherosclerosis by modifying lipid metabolism [41]. In a systematic review, Polyzos et al [42] represented the results of nine studies reporting data on 2120 participants, in regard to possible association between H. pylori infection and insulin resistance measured by a quantitative homeostatic model.…”
Section: Diabetes Mellitus and Metabolic Disordersmentioning
confidence: 99%
“…Although previous studies of the association between H. pylori and the serum lipid levels have often yielded contradictory results, those findings have generally indicated that patients with this infection have a moderately increased risk of dyslipidemia 122,124,125) . Moreover, H. pylori infection has been shown to be associated with decreased HDL cholesterol (HDL-c), apoAI and HDL-c to total cholesterol values and increased apoB levels, indicating that current infection with H. pylori is correlated with an atherogenic modified lipid profile 122,123,126) . These changes are thought to be mediated by cytokines, particularly TNF-α, which inhibits lipoprotein lipase and thus results in the mobilization of lipids from tissues as well as elevation of serum triglycerides and reductions in HDL-c 127) .…”
Section: H Pylori Related-inflammation and Atherosclerosismentioning
confidence: 99%